Coagulation dysfunction in COVID-19: the interplay between inflammation, viral infection and the coagulation system (2020)
COVID-19 is a new pandemic, caused by Severe Acute Respiratory Syndrome-CoronaVirus-2 (SARS-Cov2) infection and characterized by a broad spectrum of clinical manifestations. Inflammation and the innate immune system have been recently recognized as pivotal players in the most severe forms, characterized by significantly elevated levels of pro-inflammatory cytokines. In this setting, several studies have also reported the presence of abnormalities in coagulation parameters and platelets count, possibly identifying a subgroup of patients with poor prognosis. Some reports of full-blown thromboembolic events are emerging. Among the possible mechanisms underlying coagulation dysfunction, the so-called cytokine storm seems to play a pivotal role. Other candidate factors include virus-specific mechanisms, related to the virus interaction with renin angiotensin system (RAS) and the fibrinolytic pathway, but also comorbidities affecting these patients. Coagulation dysfunction is therefore a candidate risk factor for adverse outcomes in COVID-19 and should be carefully addressed in clinical practice.